Validity of STEM-CT Based Textbooks to Improve Students Multi-Representation Ability - Fikri, A. Mafaza Kanzul; Mahardika, I Ketut; Hariyadi, Slamet (Jurnal Paedagogy, 2024)
This research aims to describe the validity of STEM-CT-based textbooks in improving multi-representation abilities in MTs students. This study used the Research and Development (R&D) method using the 4D model, which consists of four stages, i.e., Define, Design, Develop, and Disseminate. However, this study only discussed preparing textbooks’ Define, Design, and Develop stages. The research participants were teachers of the Science MGMP in Banyuwangi. The data collection techniques used in this research were interviews, questionnaires, and validation sheets. The analysis used in this research was descriptive and qualitative. The data processing results for STEM-CT-based textbooks to improve multi-representational abilities in MTs students obtained a validity value of 82.86 in the very valid or usable category. The validation results showed that the STEM-CT-based textbooks developed could be used for classroom learning to improve students’ multi-representation abilities.